Shear‐induced platelet aggregation and distribution of thrombogenesis at stenotic vessels. (May 2017) - Kamada, Hiroki; Imai, Yohsuke; Nakamura, Masanori; Ishikawa, Takuji; Yamaguchi, Takami
ABSTRACT: Objective: SIPA, which is mediated by vWF, is a key mechanism in arterial thrombosis under an abnormally high shear rate of blood flow. We investigated the influence of SIPA on thrombogenesis, focusing on alterations in blood flow at stenotic vessels. Methods: We carried out a computer simulation of thrombogenesis in stenotic vessels at three different injury positions (ie, upstream, apex, and downstream of the stenosis) to evaluate the effect of SIPA. Results: The results demonstrated that thrombus volume increased downstream of the stenosis. In particular, growth was enhanced significantly as blood flow velocity and severity of stenosis increased. The influence of SIPA was induced by continuous exposure to high shear rate; thus, SIPA had a greater effect from the apex to downstream of the stenosis along the vessel wall. The asymmetry of the impact of SIPA contributed to the distribution of the thrombus. Furthermore, we found that the degree of SIPA was prolonged in a stenotic vessel with a distal injury, whereas it was moderate with thrombus growth in a nonstenosed vessel. This occurred because platelets and vWF that underwent a high shear rate around the apex were transported to the region downstream of the stenosis. Conclusions: These results suggest that thrombus formation downstream of the stenosis is easily affected by SIPA and hemodynamics.